Brand Image, Price, and Service Quality: Its Influence on the Decision to Purchase Toyota Brand Cars at Auto2000 Daan Mogot Jakarta - Grace Laurensia Lazuardi; Ike Kusdyah Rachmawati; Yunus Handoko (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
“Work from anywhere” trend in Jakarta has increased the need for mobility and comfort, encouraging the use of private cars, especially the Toyota brand. Toyota, a global automotive brand that was founded in 1937 in Japan, is known for its innovation, reliability, and efficiency. In Indonesia, Toyota is popular for its durable and rarely damaged vehicles. GAIKINDO data shows that Toyota is the car brand with the highest sales in Indonesia throughout 2024. One of its official dealers, Auto2000 Toyota Daan Mogot Jakarta, is the largest dealer in a strategic location with a showroom and a comfortable workshop. This study analyzes the influence of brand image, price, and service quality on the decision to purchase a Toyota car at Auto2000 Daan Mogot. The study used the technique of non-probability sampling with the accidental sampling method. Data were collected through questionnaires from 80 respondents who purchased Toyota cars from the dealer. The analysis was conducted quantitatively and descriptively using multiple linear regression with SPSS software version 26. The results of the study showed that: (1) brand image has a positive effect on purchasing decisions, (2) price has a positive effect on purchasing decisions, (3) service quality has a positive effect on purchasing decisions, and (4) simultaneously, brand image, price, and service quality have a significant effect on purchasing decisions for Toyota cars at Auto2000 Daan Mogot.